Device optimised chirp stimulus for ABR measurements with an active middle ear implant. (3rd August 2017) - Cebulla, Mario; Geiger, Ute; Hagen, Rudolf; Radeloff, Andreas
Abstract: Objective : Active middle ear implants are widely used to treat adults and children with sensorineural, conductive, or mixed hearing loss. Currently, there is no adequate method to determine the performance of active middle ear implant systems. Design : The proposed method is based on measuring the auditory brainstem response while stimulating the hearing system via the active middle ear implant (Vibrant Soundbridge TM, VSB; MEDEL, Austria). The acoustic stimulation was achieved via an optimised chirp stimulus (CE-Chirp), implemented in the Eclipse system (Interacoustics, Denmark). To compensate for the frequency-specific delays in the VSB system, the underlying model function of the CE-Chirp was adjusted accordingly (VSB-CE-Chirp). Study samples : The study includes 12 subjects having mild to profound sensorineural, conductive or mixed hearing loss. Results : The use of an optimised VSB-CE-Chirp instead of the CE-Chirp increases significantly the ABR wave V amplitudes (1.63 times) and so also increases their identifiability (by 15.2%). On average, wave V could be identified at a 7.5 dB lower stimulation level. Conclusion : The constructed VSB-CE-Chirp stimulus, after it had been transmitted through the VSB system, follows well the shape of the original CE-Chirp. Preliminary measurements in VSB patients demonstrated a significantly improved ABR amplitude with the VSB-CE-Chirp.